Local Potential and Indigenous Knowledge as a Source of Biology Research Data: Integration of Structured Observation and Digital Technology - Adinugraha, Fajar; Situmorang, Risya Pramana; Zukmadini, Alif Yanuar; Lepiyanto, Agil; Agustira, Deden (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Local potential and indigenous knowledge are important data sources in biological research because they reflect the richness of biodiversity and community knowledge that has developed from generation to generation. However, the use of these resources in research requires a structured observation approach supported by digital technology to produce reliable biological data and facilitate the preparation of scientific papers. The article aims to explore the use of local potential and indigenous knowledge as sources of biological research data through structured observation and digital technologies. The study used a literature review method, examining various scientific sources on structured observation, local potential, indigenous knowledge, digital technology, and scientific writing. The results of the study show that structured observation helps with systematic data collection by determining objects, observation aspects, documentation, and data analysis. The use of digital technologies, such as Google Search, Mendeley, Pl@ntNet, iNaturalist, GBIF, Catalogue of Life, POWO, IUCN Red List, Publish or Perish, and VOSviewer, supports the processes of searching for literature, identifying organisms, managing references, exploring biodiversity data, and analyzing research trends. The data obtained can then be communicated through the preparation of systematic scientific papers using the IMRaD structure, which includes a conclusion, appropriate citations, and informative data presentation. The integration of local potential and indigenous knowledge, structured observation, digital technology, and scientific writing contribute to the development of biological research, biodiversity documentation, preservation of indigenous knowledge, and biological resource conservation.